The SLaM Brain Health Clinic: remote biomarker enhanced memory clinic for people with mild cognitive impairment within a National Health Service mental health trust - Ashwin V. Venkataraman; Pooja Kandangwa; Roos Lemmen; Rutvi Savla; Mazda Beigi; Devon Hammond; Daniel Harwood; Justin Sauer; Latha Velayudhan; Clive Ballard; Anna-Katharine Brem; Chris Kalafatis; et al. (BJPsych Open)
Background The novel South London and Maudsley Brain Health Clinic (SLaM BHC) leverages advances in remote consultations and biomarkers to provide a timely, cost-efficient and accurate diagnosis in mild cognitive impairment (MCI).